Partnering for sustainability in agri-food supply chains: The case of Barilla Sustainable Farming in the Po Valley - Barbara Pancino; Emanuele Blasi; Anne Rappoldt; Stefano Pascucci; Luca Ruini; Cesare Ronchi (Agricultural and Food Economics, 2019)
The objective of the paper is to understand the process of designing a multi-stakeholder partnership in the adoption of sustainable innovations in value chains. More specifically, the focus is on the design of feasible types of horizontal agreements and contractual formulas to be implemented in the agri-food supply chain in order to introduce sustainable agricultural practices. To this purpose, the Barilla Sustainable Farming initiative, which is currently in the first phase of designing an MSP, is used as a case study.
Keywords: 330; Supply chain protocols; Sustainability; Crop rotation; Horizontal agreements; Contract design